A remarkable new blue Ranitomeya species (Anura: Dendrobatidae) with copper metallic legs from open forests of Juruá River Basin, Amazonia - Esteban Diego Koch; Alexander Tamanini Mônico; Jussara Santos Dayrell; Anthony Santana Ferreira; Silionamã Pereira Dantas; Jiří Moravec; Albertina Pimentel Lima (PLoS ONE, 2025)
Poison dart frogs (Dendrobatidae) are known for their aposematic coloration and toxic skin, making them a frequent subject of interest and research. However, descriptions of new species of Ranitomeya were interrupted for more than a decade. The implementation of a RAPELD (Rapid Assessment surveys of Long-Term Ecological Research) module in the Juruá River basin, a highly biodiverse and underexplored region, led to the record of a Ranitomeya species with blue dorsal stripes and coppery limbs. Herein we use morphological, morphometric, advertisement call, natural history, tadpole data and genetic data to describe the new species. Our phylogenetic analysis places the species within the Ranitomeya vanzolinii clade, and all delimitation methods confirmed its status as a new species. The species is characterized by its (i) small size (snout-vent length: males 15.2–17.0 mm, females 14.4–16.9 mm), (ii) dorsum with light sky-blue stripes on a reddish-brown ground, and metallic copper limbs with reddish-brown spots, (iii) ring-shaped granular region on the belly, (iv) toes with poorly developed lateral fringes, (v) later tadpole stages with tooth rows P1 = P2 > P3, P3 of 83–87% of P1, and conspicuous light sky-blue dorsal stripes, and (vi) cricket-like advertisement call consisting of 16–35 notes, call duration of 490–1,005 ms, note duration of 8.2–16.9 ms and dominant frequency of 5,168–6,029 Hz. The discovery of the new species emphasizes the significance of researching under-sampled regions like the Juruá River basin, and the usefulness of using a multidisciplinary approach to reveal new dendrobatid species.